Constructing Antichrist : Paul, Biblical Commentary, and the Development of Doctrine in the Early Middle Ages - Hughes, Kevin L. (Book collections on Project MUSE., 2005)
"The figure of Antichrist has gripped the Christian imagination for two thousand years. But Antichrist does not spring fully formed from the pages of Scripture. Rather, he emerges over a millennium of reflection on hints and clues scattered throughout Scripture and Christian tradition. In particular, the image of Antichrist is tied in a vital way to the man medieval Christians knew simply as 'the Apostle' - St. Paul." "Constructing Antichrist engages readers with the question : what does Paul have to do with the Antichrist? Integrating new scholarship in apocalypticism and the history of exegesis, this book is the first longitudinal study of the role of Paul in apocalyptic thought. Readers will gain new appreciation for the theological weight of medieval exegesis generally and for the persistence of apocalypticism in the medieval Christian imagination as it dared to envision the Adversary."--Jacket